Gambaran Perilaku Pencarian Pengobatan Penyakit Tuberkulosis (TB) pada Masyarakat di Wilayah Kerja Puskesmas Uitao Kecamatan Semau Kabupaten Kupang - Mayang Bukan; Ribka Limbu; Enjelita M. Ndoen (Universitas Nusa Cendana, 2020)
Treatment-seeking behavior can be seen as a reflection of the implementation of the national health system and access to health services. In the context of treatment-seeking behavior in Indonesia, the use of national health facilities. Health seeking behavior or health seeking behavior, most Indonesians will try to treat themselves first by using medicines bought at kiosks without a doctor's prescription or using traditional ingredients in the surrounding environment and even asking a traditional healer for help. If they are not successful then they go to a medical health service place, this is because Indonesia has sources of treatment covering three interconnected sectors, namely self-medication (self-medication), medical treatment and traditional medicine. However, treatment is not only conventional in nature, there are alternative treatments that are popular with the community, especially in countries rich in culture and beliefs such as Indonesia. type of research used in this research is descriptive research with a quantitative approach. This study uses a descriptive approach with the aim of describing the object of research or research results. the sampling technique using total sampling. a sample size of 209 respondents. The results showed that treatment-seeking behavior at health facilities was 41.2%, while other treatments were 58.8%. poor knowledge about TB 54.4% compared to respondents with good knowledge about TB 45.6%. positive attitude towards TB treatment was 38.2% smaller than negative attitude 61.8%. Good belief in TB treatment-seeking behavior was 36.8% smaller than bad belief about TB treatment 63.2%.